Learning through a particular trip: the tours as a resource to learn how to investigate - Chang Vargas, Giselle (2014)
At the University of Costa Rica, the tours have been used, both in workshops of the methodological analysis, as in theoretical courses in substantive axle. Its implementation in the framework of a course is not always endorsed by the faculty or by the students, because some conceive it as a walk, loss of time and institutional resources. In this paper, I will be focused in the tours as a particular trip, which is neither tour or tourism. My proposal is to conceive the tours - in the context of the social sciences - as a complementary tool to the teaching and facilitator in the teaching of research. The importance of the tours lies in its poly functional value as a teaching resource, instrument in the learning to investigate and as informational support for various projects managed by other public entities, private and communal. However, accomplish a tour is not something easy, because it is not to be mounted on a minibus and exit the field. We will show an outline of the financial, and administrative requirements, but specially those that involve planning: their relevance with one or more contents of the course; the date of execution and previous contacts. The person teaching you must go to fulfill other roles, in addition to the activities in the classroom, and that must be reinforced from certain skills, in order that the tour will benefit the students and as far as possible, for the visited community. There are alternatives to get closer to the final goal, by what we will expose two experiences of tours conducted in different courses of the major of Anthropology in different contexts and regions of the country, with different products, whose reports had different destinations and applications.